Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/sms.13464
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of stress fractures due to the female athlete triad: Differences in teens and twenties

Abstract: Background The female athlete triad (Triad), defined by the American College of Sports Medicine as low energy availability (LEA) with or without disordered eating, menstrual dysfunction, and low bone mineral density (BMD), is associated with stress fractures and athletes aged 16‐17 years are most susceptible. Purpose To examine whether the Triad increases the risk of stress fractures, athletes were assigned to a “teenage” group and a “20s” group. Methods This prospective study enrolled 390 elite female athlete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 25 publications
1
49
0
1
Order By: Relevance
“…The risk of low EA has been investigated using surrogate markers or self-reported symptoms of low EA in various athlete populations including elite para-athletes [34], adolescent/young adult [35,36] and Olympic athletes [40], female sprinters [41], male jockeys [39] and recreationally active individuals [33,37], and ranges from 14% to 63% ( Table 3). The largest cross-sectional study investigating self-reported health and performance outcomes linked to low EA and RED-S [5] placed emphasis on including body systems beyond reproductive function and bone health such as metabolic, haematological, psychological and cardiovascular health and gastrointestinal function.…”
Section: Low Energy Availability Riskmentioning
confidence: 99%
“…The risk of low EA has been investigated using surrogate markers or self-reported symptoms of low EA in various athlete populations including elite para-athletes [34], adolescent/young adult [35,36] and Olympic athletes [40], female sprinters [41], male jockeys [39] and recreationally active individuals [33,37], and ranges from 14% to 63% ( Table 3). The largest cross-sectional study investigating self-reported health and performance outcomes linked to low EA and RED-S [5] placed emphasis on including body systems beyond reproductive function and bone health such as metabolic, haematological, psychological and cardiovascular health and gastrointestinal function.…”
Section: Low Energy Availability Riskmentioning
confidence: 99%
“…The American College of Sports Medicine (ACSM) defines the Female Athlete Triad (Triad) as low energy availability (LEA) with or without disordered eating, menstrual dysfunction, and low BMD 1 . This Triad increases the risk of bone stress fractures 4,14 . However, there are few established pharmacological treatments for low BMD in athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Stress fractures occur as a result of repetitive mechanical loading. Female athletes are at a higher risk of stress fractures than male athletes, with a frequency of 1–3% in male athletes and 10–12% in female athletes . Moreover, it has been reported that the frequency of stress fractures among 1616 female athletes and 537 controls (non‐athletes) was 22.6% for athletes competing at the international level, 23.3% for athletes competing at the national level, 20.8% for athletes competing at the local level, 18.8% for athletes competing at other levels and 4.3% for controls .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the frequency of stress fractures among 1616 female athletes and 537 controls (non‐athletes) was 22.6% for athletes competing at the international level, 23.3% for athletes competing at the national level, 20.8% for athletes competing at the local level, 18.8% for athletes competing at other levels and 4.3% for controls . Stress fractures are associated with the Female Athlete Triad (Triad), which is defined by the American College of Sports Medicine (ACSM) as low energy availability with or without disordered eating, menstrual dysfunction and low bone mineral density. Barrack et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation